THE ROLE OF ISLAMIC BANKS IN PROMOTING THE GROWTH OF MICRO, SMALL, AND MEDIUM-SIZED ENTERPRISES (MSMEs) IN INDONESIA (A REVIEW OF THE MAQASHID AL-SHARIAH) - M. Asri Setiawan; Zaiful Anas Qiblatain (IZZI: Jurnal Ekonomi Islam, 2026)
This study aims to analyze the role of Islamic banks in promoting the growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia from the perspective of maqashid sharia. This research employs a qualitative descriptive approach using literature review and secondary data analysis obtained from the Financial Services Authority (OJK), Bank Indonesia, and relevant scientific publications from 2018–2023. The results indicate that Islamic bank financing, particularly through murabahah, musyarakah, and mudharabah contracts, significantly contributes to improving MSMEs' access to capital and fostering economic justice. However, challenges remain in terms of low Islamic financial literacy and the dominance of sale-based contracts over profit-sharing schemes. This study is expected to provide academic and practical contributions to the development of Islamic banking oriented toward public welfare.